Perception of the Retailers Towards Marketing Mix Strategies: An Empirical Case Study on the Soft Drink Market in Visakhapatnam - Devi Prasad Kotni, V. V. (Indian Journal of Marketing, 2014)
Marketing mix is a powerful tool that enables the marketers to concentrate on specific marketing tasks specialization wise (4Ps) and allocate the resources like money, time, and efforts to these tasks to be successful in marketing of products. On the other hand, retailing is the task of selling products to the final customers who are influenced by the marketers or by the retailers to make a purchase. The present case study mainly focuses on retailers’ perception of the marketing mix strategies adopted by major players in the Indian soft drink market, that is, Coca-Cola and Pepsi. The study was conducted in Visakhapatnam with an objective of conducting a comparative analysis on the perceptions of the retailers towards the marketing mix strategies adopted by these organizations. The primary data was collected from 100 retailers in Visakhapatnam city who were selling both Coca-Cola and Pepsi products in their outlets. This case study enables the readers to practically analyze how the marketing mix strategies are implemented in the soft drink market and how well the strategies are received by the retailers.